2022
DOI: 10.1002/art.41229
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Bone Changes Are Associated With Broad‐Spectrum Autoimmunity and Predict the Onset of Rheumatoid Arthritis

Abstract: Objective. To assess if microstructural bone lesions in individuals at risk of developing rheumatoid arthritis (RA) are related to the spectrum of anti-modified protein antibodies (AMPAs) and affect the risk of developing RA.Methods. Cortical microchannels as well as cortical and trabecular bone mineral density (BMD) volumes (expressed as mg hydroxyapatite/cm 3 ) were analyzed by high-resolution peripheral quantitative computed tomography of the hand joints of individuals at risk of RA. AMPA response was profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
7
0
2
Order By: Relevance
“…Accumulating evidence suggests that miRNAs regulate 1/3rd of the human genome via translational inhibition or degradation of the cognate genes, and form complex regulatory networks that have been implicated in malignant progression [10,11]. Aberrant expression of miRNAs has been detected in RAassociated in ammatory innate immune responses, and they are increasingly being considered as prognostic biomarkers as well as therapeutic targets [12,13]. For example, Yu et al showed that miR-92a could target AKT2 to inhibit broblast-like synoviocyte proliferation and migration in RA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that miRNAs regulate 1/3rd of the human genome via translational inhibition or degradation of the cognate genes, and form complex regulatory networks that have been implicated in malignant progression [10,11]. Aberrant expression of miRNAs has been detected in RAassociated in ammatory innate immune responses, and they are increasingly being considered as prognostic biomarkers as well as therapeutic targets [12,13]. For example, Yu et al showed that miR-92a could target AKT2 to inhibit broblast-like synoviocyte proliferation and migration in RA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that miRNAs regulate 1/3rd of the human genome via translational inhibition or degradation of the cognate genes, and form complex regulatory networks that have been implicated in malignant progression [10,11]. Aberrant expression of miRNAs has been detected in RAassociated inflammatory innate immune responses, and they are increasingly being considered as prognostic biomarkers as well as therapeutic targets [12,13]. For example, Yu et al showed that miR-92a could target AKT2 to inhibit fibroblast-like synoviocyte proliferation and migration in RA [14].…”
Section: Discussionmentioning
confidence: 99%
“…Interessanterweise konnten hochauflösende CT-Studien das Konzept der strukturellen Veränderung der Gelenke durch Autoimmunität vor dem Beginn der entzündlichen Phase der Erkrankung stützen. So konnte kürzlich gezeigt werden, dass mikrostrukturelle Veränderungen (Cortical micro-channels [CoMiCs]) [16] bei RA-at-risk-Personen mit einer Breitspektrum-Autoimmunität verbunden sind und den Ausbruch einer klinisch manifesten RA voraussagen [15]. Auch weitere CT-Arbeiten konnten die Bedeutung der Autoimmunität für den Knochen hervorarbeiten.…”
Section: Computertomografie Bei Der Rheumatoiden Arthritisunclassified
“…Jedoch können CT-Forschungs ergebnisse einen wertvollen Beitrag zu einem besseren Verständnis der Krankheit sowie des Therapieansprechens leisten. Insbesondere Studien unter Verwendung der hochauflösenden peripheren quantitativen Computertomografie (HR-pQCT) waren hierbei in den letzten Jahren hilfreich [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
unclassified